Multidisciplinary information retrieval : 6th Information Retrieval Facility Conference, IRFC 2013, Limassol, Cyprus, October 7-9, 2013. Proceedings - Kanoulas, Evangelos; Loizides, Fernando; Lupu, Mihai (Lecture Notes in Computer Science, 2013)
This book constitutes the proceedings of the 6th International Information Retrieval Facility Conference, IRFC 2013, held in Limassol, Cyprus, October 2013. The 8 papers presented together with 2 short papers were carefully reviewed and selected from 16 high-quality submissions. IRF conferences wish to bring young researchers into contact with industry at an early stage. This sixth conference aimed to tackle four complementary research areas: information retrieval, machine translations for search solutions, and interactive information access.